Compensation for land rights holders according to the land acquisition law - Dhaniar Eka Budiastanti; Khotbatul Laila; Nahdiya Sabrina; Diah Aju Wisnuwardhani; Selvia Wisuda (Jurnal Cakrawala Hukum, 2022)
The aspect of compensation is very crucial in land acquisition for development for the public interest. The Law of the Republic of Indonesia Number 2 of 2012 concerning Land Procurement for Development in the Public Interest (PTBPKU Law) is "drowned" by the many cases of land disputes that are so complex. The regulations regarding land acquisition contained in the PTBPKU Law are indeed correct, but when viewed in terms of substance, they still leave several separate notes. Several things need to be studied more deeply, primarily related to the basic concept of acquiring land rights for the public interest and compensation assessment. This paper aims to provide legal protection for land rights holders who reject the amount of payment in the PTBPKU Law and compare it with the latest regulation of land acquisition, namely the Job Creation Act. The writing method used is a normative juridical method using the Statute Approach and the Comparative Approach. The PTBPKU Law, as amended by the Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation, has not been able to fully protect the holders of land rights affected by land acquisition for development in the public interest. Regulators should pay more attention to matters relating to compensation for land rights holders.How to cite item:Â Budiastanti, D., Laila, K., Sabrina, N., Wisnuwardhani, D., Wisuda, S. (2022). Compensation for land rights holders according to the land acquisition law.Â Jurnal Cakrawala Hukum, 13(2), 135-144. DOI:https://doi.org/10.26905/idjch.v13i2.7970.